Generative AI and Da'wah Management Integration: Strengthening SEL and Global Citizenship Education for SDG 4 in Indonesia - Zainul Arifin; Wa Selni Imran (Assyfa Journal of Multidisciplinary Education, 2025)
Strengthening Social Emotional Learning (SEL) and Global Citizenship Education (GCED) has become a crucial global mandate to shape 21st-century student competencies and support the achievement of SDG 4 (Quality Education) in Indonesia. Although social media platforms offer authentic spaces for emotional resonance and identity formation, interactions within them are often shallow and lack sustained critical reflection. This gap challenges ethical and moral education efforts, including religious-based ones such as Da'wah Management. This position paper aims to propose and verify a conceptual model for integrating Generative Artificial Intelligence (GenAI) with Da'wah Management principles to improve the quality and effectiveness of SEL and GCED delivery in the Indonesian educational context. The approach used is a conceptual position paper involving a comprehensive literature review, analysis of national education policies, and construction of a theoretical framework linking transformative technology with character education. The main argument of this research is that GenAI functions as a reflective and adaptive layer that can transform the implementation of Da'wah Management and character education. GenAI overcomes the limitations of social media by providing personalized feedback, presenting in-depth ethical scenario simulations, and facilitating critical dialogue, thereby fostering empathetic and responsible digital citizenship. This proposed integration framework for GenAI and Da'wah Management has significant implications for curriculum developers and educators, offering a robust technology-based strategy to prepare Indonesian youth as ethical, socially conscious global citizens, while simultaneously accelerating the realization of Target 4.7 of SDG 4: Quality Education.